Considerations of low carbohydrate availability (LCA) to relative energy deficiency in sport (RED-S) in female endurance athletes: a narrative review - Lodge, M. T.; Ward-Ritacco, C. L.; Melanson, K. J. (Nutrients, 2023)
The purpose of this narrative review is to identify health and performance consequences associated with LCA in female endurance athletes. The intake of carbohydrates (CHO) before, during, and after exercise has been demonstrated to support sport performance, especially endurance activities which rely extensively on CHO as a fuel source. However, low energy availability (LEA) and low carbohydrate availability (LCA) are common in female athletes. LEA occurs when energy intake is insufficient compared to exercise energy expenditure, and LEA-related conditions (e.g., Female Athlete Triad (Triad) and Relative Energy Deficiency in Sport (RED-S)) are associated with a myriad of health and performance consequences. The RED-S model highlights 10 health consequences and 10 performance consequences related to LEA. The independent effect of LCA on health and performance has been under-researched, despite current CHO intake being commonly insufficient in athletes. It is proposed that LCA may not only contribute to LEA but also have independent health and performance consequences in athletes. Furthermore, this review highlights current recommendations for CHO intake, as well as recent data on LCA prevalence and menstrual cycle considerations. A literature review was conducted on PubMed, Science Direct, and ResearchGate using relevant search terms (i.e., "low carbohydrate/energy availability", "female distance runners"). Twenty-one articles were identified and twelve met the inclusion criteria. The total number of articles included in this review is 12, with 7 studies illustrating that LCA was associated with direct negative health and/or performance implications for endurance-based athletes. Several studies included assessed male athletes only, and no studies included a female-only study design. Overall, the cumulative data show that female athletes remain underrepresented in sports science research and that current CHO intake recommendations and strategies may fail to consider female-specific adaptations and hormone responses, such as monthly fluctuations in estrogen and progesterone throughout the menstrual cycle. Current CHO guidelines for female athletes and exercising women need to be audited and explored further in the literature to support female athlete health and performance.